Advanced Colloidal Lithography Beyond Surface Patterning. Issue 1 (22nd June 2016) - Ai, Bin; Möhwald, Helmuth; Wang, Dayang; Zhang, Gang
Abstract : This Review presents an overview of recent development of colloidal lithography (CL) and its applications in fabrication of various nanostructures consisted of orderly arranged, dots, holes, bowls, cones, pillars, rings, shells and triangles. These structures have been widely exploited in various fields, including plasmonics, optics, wettability, sensors, solar cells, organic light‐emitting diode (OLEDs), biology and many others. The recent successes in the technical applications of the nanostructures fabricated via CL will be summarized. Hopefully, the present review will inspire more ingenious designs and execution of CL for advanced, smart applications. Abstract : This paper reviews recent development of colloidal crystal masks and applications of typical structures fabricated by colloidal lithography in plasmonics, wettability, biology, solar cells and etc., aiming at inspiration of ingenious combination of colloidal technique with practical applications.